A Primer on Luminescence Sensing. Issue 2 (30th January 2023) - Gorris, Hans H.; Farka, Zdeněk; Hildebrandt, Niko
Abstract: This Perspective provides a concise overview of the field of Luminescence Sensing, which enables highly sensitive, selective, and versatile measurements. The emergence of new luminescent nanomaterials and the prospective of deploying new luminescence‐based detection schemes for solving real‐world problems, e. g., in medical diagnosis, food safety, and environmental sciences, has led to a continuous growth of the field over recent years. The contributions to the Special Collection on Luminescence Sensing – with a focus on the versatility and advantages of lanthanide complexes for advanced biosensing – serve as an excellent foundation to highlight and discuss recent developments and challenges. Abstract : Considering the very young age of Analysis & Sensing (launched in 2021) and the very old age of luminescence sensing (dating back two centuries), we are delighted to present seven original research articles and one review article in the Special Collection on Luminescence Sensing . We would like to thank the authors, reviewers, and editors for their valuable contributions.